2014
DOI: 10.5194/cp-10-1763-2014
|View full text |Cite
|
Sign up to set email alerts
|

Millennial minimum temperature variations in the Qilian Mountains, China: evidence from tree rings

Abstract: Abstract.A 1343-year tree-ring chronology was developed from Qilian junipers in the central Qilian Mountains of the northeastern Tibetan Plateau (TP), China. The climatic implications of this chronology were investigated using simple correlation, partial correlation and response function analyses. The chronology was significantly positively correlated with temperature variables prior to and during the growing season, especially with monthly minimum temperature. Minimum temperature anomalies from January to Aug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 93 publications
2
23
0
Order By: Relevance
“…On the southeastern TP, the cold period from 1816 to 1822 may have also been related to the Tambora eruption (Liang et al, 2008). Other research in the northeastern TP has shown that cold years can be matched with known tropical volcanic events in 15 of 21 cases (Zhang et al, 2014). We compared the years of cooling we identified in this study with those identified by Zhang et al (2014) and found that the cooling years are either the same or within a year of each other.…”
Section: The Effect Of Volcanic Activity On the Reconstructed T Min 87mentioning
confidence: 61%
See 4 more Smart Citations
“…On the southeastern TP, the cold period from 1816 to 1822 may have also been related to the Tambora eruption (Liang et al, 2008). Other research in the northeastern TP has shown that cold years can be matched with known tropical volcanic events in 15 of 21 cases (Zhang et al, 2014). We compared the years of cooling we identified in this study with those identified by Zhang et al (2014) and found that the cooling years are either the same or within a year of each other.…”
Section: The Effect Of Volcanic Activity On the Reconstructed T Min 87mentioning
confidence: 61%
“…Qilian juniper samples were taken from a natural woodland 35 km west of Ningmute town, Henan County, Qinghai Province, China (100.96 • E, 34.62 • N, 3806 m a.s.l.). This area is located in the sub-frigid zone and has a semi-humid climate (Zheng et al, 2013). According to climate data of the Henan meteorological station ; Table 1), mean annual temperature is 0.31 • and mean annual precipitation is 582 mm.…”
Section: Tree-ring Datamentioning
confidence: 99%
See 3 more Smart Citations